The Astral Library : a novel [compact disc, unabridged] - Quinn, Kate (HarperAudio, 2026)
Working three dead-end jobs to make ends meet, Alexandria "Alix" Watson takes nightly refuge in the high-vaulted reading room at the Boston Public Library, escaping into her favorite fantasy novels and dreaming of far-off lands. One day she stumbles through a hidden door and meets the Librarian: the ageless, acerbic guardian of a hidden library where the desperate and the lost escape to new lives inside their favorite books. The Librarian takes a dazzled Alix under her wing, but before she can escape into the pages of her new life, a shadowy enemy emerges to threaten everyone the Astral Library has ever helped to protect.